PERILAKU MASYARAKAT DAN KAITANNYA DENGAN PERSEPSI TERHADAP RUMAH SEHAT DI DUSUN KEBONAN, DESA TOLOKAN, KECAMATAN GETASAN, KABUPATEN SEMARANG - Puspita, Dhanang; Sujana, Treesia; Safitri, Lia Herlyn (KRITIS, 2019)
Perception is the result of the sensing process and the process of observing someone about something that will result in a behavioral response. Human behavior is a response to stimuli both from within and outside the individual. A healthy house is a house that meets the technical terms and conditions to protect the occupants of the house from various threats and health problems, so that an optimal health degree can be achieved. The percentage of healthy houses nationally is 61.81% and Central Java province has reached 70.40%, however, in Kebonan hamlet which is located in Central Java Province has a low percentage of healthy houses, only 9%. The research aim to describe the perception of the community about a healthy house and its relation to health behavior. The research method used is descriptive qualitative, data collection was carried out by in-depth interviews and processed into verbatim then analyzed and the validity of the results tested by source triangulation. From the research results, it can be seen that the public's understanding of a healthy house in general is still limited, the public perception of the benefits of a healthy house and the disadvantages of a less healthy house is good enough, but the method of treating community waste is still not good. The efforts that can be made by the community to maintain a healthy house are still not maximal because of limited information. The low percentage of healthy houses in Kebonan hamlet is caused by poor behavior in managing houses and household waste. Limited information affects people's perceptions about a healthy home and results in not maximizing community behavior in running a healthy house. Perceptions of a healthy home and health behavior of some people in Kebonan hamlet are interrelated, so that to form good behavior knowledge needs to be increased in order to form a good perceptual understanding and positive behavior.